2012
DOI: 10.1128/aac.05420-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Environment and Stability of cfr in Methicillin-Resistant Staphylococcus aureus CM05

Abstract: The Cfr methyltransferase confers resistance to many 50S ribosomal subunit-targeted antibiotics, including linezolid (LZD), via methylation of the 23S rRNA base A2503 in the peptidyl transferase center. Methicillin-resistant Staphylococcus aureus strain CM05 is the first clinical isolate documented to carry cfr. While cfr is typically plasmid borne, in CM05 it is located on the chromosome and is coexpressed with ermB as part of the mlr operon. Here we evaluated the chromosomal locus, association with mobile ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 54 publications
1
41
0
3
Order By: Relevance
“…However, in some clinical isolates of S. aureus, cfr coexpressed with the erm gene, which encodes a methyltransferase with another targeting 23S rRNA residue, A2058. The dimethylation of A2058 by Erm increases the fitness cost associated with Cfr-mediated methylation of A2503 (173,174).…”
Section: Resistance To Oxazilidones (Linezolid) and Effect On Virulencementioning
confidence: 99%
“…However, in some clinical isolates of S. aureus, cfr coexpressed with the erm gene, which encodes a methyltransferase with another targeting 23S rRNA residue, A2058. The dimethylation of A2058 by Erm increases the fitness cost associated with Cfr-mediated methylation of A2503 (173,174).…”
Section: Resistance To Oxazilidones (Linezolid) and Effect On Virulencementioning
confidence: 99%
“…Since its initial identification on the multiresistance plasmid pSCFS1 from Staphylococcus sciuri in 2000 (21), several studies have reported the cfr gene in staphylococcal isolates of animal and human origin. In most reports, the cfr gene was located on different plasmids (9,10,16), while in a few cases, it was also detected in the chromosomal DNA (9,14,27). Recently, the first outbreak case of linezolid-resistant, cfr-carrying Staphylococcus aureus was reported in Spain (17), and the cfr gene has also been identified in Panton-Valentine leukocidin-positive sequence type 8 (ST8) methicillin-resistant S. aureus IVa (USA300) (23).…”
mentioning
confidence: 99%
“…In this S. aureus isolate, designated CM05, the cfr gene was located in the chromosome, and its genetic environment differed greatly from that seen in the plasmids (19,26,27). In the CM05 isolate, cfr is located immediately downstream of the Tn917-derived gene erm(B), which encodes a methyltransferase that modifies A2058 in 23S rRNA and confers resistance to macrolides, lincosamides, and streptogramin B.…”
mentioning
confidence: 99%
“…The 1.5-kb cfr-containing region is inserted in the 23S rRNA gene of the rrn4 allele. Active transcription of the rRNA operon might contribute to cfr expression in the CM05 isolate (27).…”
mentioning
confidence: 99%